Ultrasensitive Hierarchical Piezoresistive Pressure Sensor for Wide‐Range Pressure Detection - Jing Li; Tianyu Wu; Huan Jiang; Yanyu Chen; Qibiao Yang (Advanced Intelligent Systems, 2021)
Pressure sensitivity and wide range are two crucial features of flexible electromechanical sensors for applications in the next‐generation of intelligent electronics, such as wearable healthcare monitors and soft human–machine interfaces. Conventional pressure sensors have a narrow pressure range (<10 kPa) and complex fabrication processes, which significantly hinder their extensive applications. A facile laser‐engraving method is proposed to fabricate a flexible multiwalled‐carbon‐nanotube (MWCNTs)/poly(dimethylsiloxane) (PDMS) composite‐based piezoresistive sensor with hierarchical microstructures. Herein, the nonstandard‐circular feature and Gaussian distributed facula of a laser spot are utilized to produce the middle‐level porous microdome upon the bottom‐level cylinder microcolumn array, while the top‐level tentacle‐like conical micropillars are produced by vertically rotating the acrylic mold during the laser engraving process. This novel hierarchical microstructure endows the proposed piezoresistive sensor with orders‐of‐magnitude of higher sensitivity (≈35.51 kPa−1) than that of other reported electromechanical sensors and a more extensive pressure sensing range up to 23 kPa. Moreover, the detection limit of the sensor is down to 2 Pa, which makes it a desirable candidate for monitoring subtle pressure. The sensor is successfully applied to distinguish the syllables of each pronounced word, detect movements of the human wrist, and monitor radial arterial pulse, thus demonstrating its promising applications in wearable electronics.